EFFECT OF PRODUCTIVE ZAKAT DISTRIBUTION ON IMPROVING THE STANDARD OF LIFE OF MUSTAHIK IN BEKASI CITY BAZNAS - Muhammad Asmawi (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2022)
Zakat is an obligation for Muslims. Zakat is a social worship that is intended as an equalizer. Zakat is also a tool that can be used to eliminate the income gap between those who are well off and those who still feel deprived. As we know, productive zakat can be used by mustahik in developing his business so as to increase income and improve his standard of living, even removing himself from a mustahik to become a muzaki. Because, with this productive zakat distribution pattern, BAZNAS will be more careful in studying the problem of poverty which can be caused by a lack of working capital, no job opportunities and a lack of education as a concept of planning and implementation. With this productive zakat distribution pattern, it is hoped that it can help the community in alleviating poverty by increasing the standard of living of its mustahik. The contract used by BAZNAS in Bekasi city is a grant contract, namely giving free of charge to mustahik. Zakat adalah sebuah kewajiban bagi ummat Islam. Zakat merupakan suatu ibadah sosial yang diperuntukan sebagai pemerata. Zakat juga merupakan salah satu alat yang dapat dipergunakan untuk menghilangkan kesenjangan pendapatan antara yang berkecukupan dengan yang masih merasa kekurangan. Seperti kita ketahui seharusnya zakat produktif dapat dipergunakan oleh mustahik dalam mengembangkan usahanya sehingga meningkatkan pendapatan dan meningkatkan taraf hidupnya, bahkan mengeluarkan dirinya dari mustahik menjadi seorang muzaki. Karena, dengan pola pendistribusian zakat produktif ini, BAZNAS akan lebih cermat dalam mengkaji persoalan kemiskinan yang bisa disebabkan karena kurangnya modal kerja, tidak adanya kesempatan kerja dan minimnya pendidikan sebagai konsep perencanaan dan pelaksanaan. Dengan pola pendistribusian zakat produktif ini diharapkan dapat membantu masyarakat dalam mengentaskan kemiskinan dengan cara meningkatkan taraf hidup para mustahiknya.. Adapun akad yang dipakai BAZNAS kota Bekasi adalah akad hibah yaitu pemberian secara cuma-cuma kepada mustahik.